Обґрунтування та структуризація системи показників для проведення моніторингу земель сільськогосподарського призначення - Гарнець, С. В. (Ways to Improve Construction Efficiency, 2012)
In the article shows the practical advantages of using technologies of remote sensing during the work on monitoring of land for agricultural purpose, and the proposed structure of indicators for monitoring.